2008
DOI: 10.3758/mc.36.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Prior knowledge enhances the category dimensionality effect

Abstract: A study of the combined influence of prior knowledge and stimulus dimensionality on category learning was conducted. Subjects learned category structures with the same number of necessary dimensions but with more or fewer additional, redundant dimensions and with either knowledge-related or knowledge-unrelated features. Minimal-learning models predict that all subjects, regardless of condition, either should learn the same number of dimensions or should respond more slowly to each dimension. Despite similar le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…But blocking was eliminated when subjects predicted letter strings instead (''Mobbles" or ''Streaths") that were plausibly the labels of actual categories (of automobiles, given that the ''cues" were features of cars). Finally, Hoffman, Harris, and Murphy (2008) demonstrated that subjects will learn far more than necessary about a new category when subjects can use their prior knowledge to relate the new category to previously learned concepts. In each of these studies, subjects could succeed at the experimental task without learning anything else about the categories, and yet they learned more nonetheless.…”
Section: A New Model Of Feature Inference Learningmentioning
confidence: 97%
“…But blocking was eliminated when subjects predicted letter strings instead (''Mobbles" or ''Streaths") that were plausibly the labels of actual categories (of automobiles, given that the ''cues" were features of cars). Finally, Hoffman, Harris, and Murphy (2008) demonstrated that subjects will learn far more than necessary about a new category when subjects can use their prior knowledge to relate the new category to previously learned concepts. In each of these studies, subjects could succeed at the experimental task without learning anything else about the categories, and yet they learned more nonetheless.…”
Section: A New Model Of Feature Inference Learningmentioning
confidence: 97%
“…For instance, when provided with an occupational label, individuals tend to remember both more consistent and inconsistent information compared to when no label is provided (Cohen, 1981). Hoffman, Harris, and Murphy (2008) investigated university students' ability to learn information about given categories that had five or 10 dimensions. The results indicated that not only did prior knowledge increase learning of new information about given categories, but that the more dimensions participants were exposed to, the more they learned even beyond what they were told they would be assessed on.…”
Section: The Effects Of Prior Knowledge On Recallmentioning
confidence: 99%
“…En algunos casos el concepto puede hacer el procesamiento más eficiente. Por ejemplo, durante el aprendizaje de un concepto nuevo, el hecho de poseer un concepto previo relacionado lo hace más fácil de aprender (Clapper, 2007;Hoffman, Harris & Murphy, 2008;Kaplan & Murphy, 2000;Murphy & Allopenna, 1994). Sin embargo, y al mismo tiempo, poseer un concepto puede introducir errores o sesgos (e.g., Elischberger, 2005).…”
Section: Los Estereotipos De Género Como Conceptosunclassified